EFEKTIVITAS PELAKSANAAN MANAJEMEN BERBASIS SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI SD N 3 SESETAN - Chindytia; Anak Agung Gede Agung; Luh Made Lely Pradnyani; Luh Ayu Pradnyawati; I Gusti Ngurah Angga Diatmika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effectiveness of the implementation of School-Based Management (SBM) in improving the quality of education at SD Negeri 3 Sesetan. This research employed a qualitative approach with a descriptive method to obtain an in-depth understanding of the implementation of SBM in the school environment. Data were collected through in-depth interviews, direct observation, and documentation studies involving Ketut Suci Antari, S.Pd., one of the teachers at SD Negeri 3 Sesetan, as the main informant. The findings revealed that the implementation of SBM at SD Negeri 3 Sesetan has been carried out effectively and systematically since the school was established. The implementation of SBM has positively impacted the quality of learning, school management effectiveness, resource efficiency, and teacher productivity. School programs are designed based on the school’s vision and mission and adjusted to students’ needs and environmental conditions. Stakeholder involvement, including principals, teachers, parents, the community, and the government, also plays an important role in supporting the success of SBM implementation. Monitoring and evaluation activities are conducted regularly to improve and sustain school programs. However, the school still faces challenges related to funding limitations in supporting all flagship programs optimally. Based on the SWOT analysis, the school’s strengths lie in its flagship programs and strong stakeholder synergy, while funding remains the main weakness. Overall, the implementation of SBM at SD Negeri 3 Sesetan has proven effective in improving educational quality and creating a more participatory, efficient, and sustainable school management system. Keywords: School-Based Management, Education Quality, Effectiveness, Elementary School